2002
DOI: 10.4314/wsa.v28i1.4875
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of a recycling sludge bed reactor using AQUASIM: reprint

Abstract: re-published with the correct list of authors, and, due to a change in the process name following the original publication of the article, it is herewith pointed out that the term "falling sludge bed reactor" is replaced with "recycling sludge bed reactor".Modelling of a recycling sludge bed reactor using AQUASIM AbstractThe recycling sludge bed reactor (RSBR) allows for increased solids retention time, resulting in greater substrate conversion for all particulate degradation and biological reactions. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…Kinetics of sulfate reduction processes have been considered in different ways. A dual term Monod type kinetic is commonly used (Equation ) to represent the bacterial growth rate (ρ growth ), with both concentrations: sulfate (normalSSO4) as electron acceptor and the electron donor (S i ) (hydrogen or organic matter) following the equations of Table . The expression is generally written in the form of substrate uptake (ρ uptake ) by dividing the maximum specific growth rate (μ max ) by the yield of biomass on the substrate (μ max /Y = k m ) to obtain Equation .…”
Section: Dynamic Modeling Of Sulfate Reduction Processes In the Anaersupporting
confidence: 60%
See 2 more Smart Citations
“…Kinetics of sulfate reduction processes have been considered in different ways. A dual term Monod type kinetic is commonly used (Equation ) to represent the bacterial growth rate (ρ growth ), with both concentrations: sulfate (normalSSO4) as electron acceptor and the electron donor (S i ) (hydrogen or organic matter) following the equations of Table . The expression is generally written in the form of substrate uptake (ρ uptake ) by dividing the maximum specific growth rate (μ max ) by the yield of biomass on the substrate (μ max /Y = k m ) to obtain Equation .…”
Section: Dynamic Modeling Of Sulfate Reduction Processes In the Anaersupporting
confidence: 60%
“…In general, substrate competition in anaerobic systems has been modeled in most cases on three levels (I, II and III) (Fig. ) . Starting from the volatile fatty acids, butyrate and propionate sulfate reducing bacteria (bSRB and pSRB respectively) compete with acetogenic bacteria to form hydrogen sulfide, carbon dioxide, water and acetic acid (level I).…”
Section: Dynamic Modeling Of Sulfate Reduction Processes In the Anaermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that S h2s has been found to inhibit anaerobic digestion (Visser et al, 1996), S h2s,free was assumed to be inhibitory for modeling purposes Knobel and Lewis, 2002;Ristow et al, 2002). A non-competitive inhibition function for sulfides (I h2s,j ) was considered in all cases (Knobel and Lewis, 2002).…”
Section: Model Description and Implementationmentioning
confidence: 99%
“…The simple approach of Batstone (2006) to model sulfate reduction as an extension of ADM1 has been used to model the anaerobic digestion of vinasse under dynamic conditions without success, exhibiting under prediction of H 2 S and over prediction of volatile fatty acids (Hinken et al, 2013). In order to extend ADM1, Fedorovich et al (2003) included the sulfate reduction process starting from previously reported work Knobel and Lewis, 2002;Ristow et al, 2002). The approach of Fedorovich et al (2003) can be considered as complex because of the inclusion of valerate/ butyrate, propionate, acetate and hydrogen in the sulfate degradation reactions (Batstone, 2006).…”
Section: Introductionmentioning
confidence: 99%